2023
DOI: 10.15252/embr.202256702
|View full text |Cite
|
Sign up to set email alerts
|

Piccolino is required for ribbon architecture at cochlear inner hair cell synapses and for hearing

Abstract: Cochlear inner hair cells (IHCs) form specialized ribbon synapses with spiral ganglion neurons that tirelessly transmit sound information at high rates over long time periods with extreme temporal precision. This functional specialization is essential for sound encoding and is attributed to a distinct molecular machinery with unique players or splice variants compared to conventional neuronal synapses. Among these is the active zone (AZ) scaffold protein piccolo/aczonin, which is represented by its short splic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 92 publications
(233 reference statements)
0
6
0
Order By: Relevance
“…Changes in Ca 2+ channel physiology upon deletion of RIBEYE were also found for CaV1.4 at ribbon-less rod photoreceptor AZs (Grabner & Moser, 2021). Finally, IHCs lacking piccolino, a ribbonsynapse specific isoform of the AZ protein piccolo, show AZs with smaller synaptic ribbons and altered clustering yet normal complement of Ca 2+ channels (Michanski et al, 2023).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Changes in Ca 2+ channel physiology upon deletion of RIBEYE were also found for CaV1.4 at ribbon-less rod photoreceptor AZs (Grabner & Moser, 2021). Finally, IHCs lacking piccolino, a ribbonsynapse specific isoform of the AZ protein piccolo, show AZs with smaller synaptic ribbons and altered clustering yet normal complement of Ca 2+ channels (Michanski et al, 2023).…”
Section: Introductionmentioning
confidence: 73%
“…We note that other ribbon-resident proteins such as piccolino likely contribute to this fine-tuning of the size and shape of ribbon-type AZs. Indeed, disruption of piccolino in IHCs reduced the average ribbon size (Müller et al, 2019;Michanski et al, 2023). One exciting example of ribbon synapse heterogeneity manifests itself in IHCs where synapses show a spatial size gradient that likely relates to the diverse molecular and functional properties of the postsynaptic SGNs (reviewed in Moser et al, 2023).…”
Section: Synthetic Active Zone Reconstitution Model To Study Ribbon S...mentioning
confidence: 99%
“…In mice, work has shown that in sensory cells lacking Bassoon ribbons are not properly anchored at the presynaptic AZ, and synapse function is disrupted (Dick et al, 2003; Frank et al, 2010; Khimich et al, 2005). In rats, loss of Piccolino also impacts ribbon morphology (Michanski et al, 2023; Regus-Leidig et al, 2014). Currently how these key molecular players fit within the dynamics underlying ribbon formation is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Such ‘free-floating’ ribbon precursors can occur at significant distances to the AZ and have previously been observed not only in auditory IHCs, but also pinealocytes and retinal photoreceptors (Hermes et al, 1992; Regus-Leidig et al, 2009; Spiwoks-Becker et al, 2008, 2004). Across all systems, floating precursors were shown to tether a cohort of SVs and consist not only of the main scaffold RIBEYE, but also contain other AZ proteins such as Piccolino, a short splice variant of Piccolo (Michanski et al, 2023, 2019; Regus-Leidig et al, 2013). Hence, these precursors can be considered as presynaptic ‘building blocks’ for rapid AZ establishment or supplementation at nascent afferent contacts.…”
Section: Introductionmentioning
confidence: 99%